Does barefoot running decrease the risk of injuries in runners?. Issue 2 (February 2017) - Blanco, Noel; Blanco, Paris
Abstract : EVIDENCE‐BASED ANSWER : There is insufficient patient‐oriented evidence to determine if barefoot running decreases the total number of injuries in runners. Barefoot running is associated with mechanical changes that decrease stress on the knee, but increase stress on the ankle (SOR: C, meta‐analysis of observational studies using disease‐oriented outcomes). Traditional shoe runners report higher rates of lower extremity injuries than minimalist shoe runners (SOR: C, online survey).